2014
DOI: 10.1002/prot.24538
|View full text |Cite
|
Sign up to set email alerts
|

WeFold: A coopetition for protein structure prediction

Abstract: The protein structure prediction problem continues to elude scientists. Despite the introduction of many methods, only modest gains were made over the last decade for certain classes of prediction targets. To address this challenge, a social-media based worldwide collaborative effort, named WeFold, was undertaken by thirteen labs. During the collaboration, the labs were simultaneously competing with each other. Here, we present the first attempt at “coopetition” in scientific research applied to the protein st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 64 publications
2
40
0
2
Order By: Relevance
“…Cursory analysis of to-date results suggests that progress has so far been fairly limited [3]. Similarly, the recently published outcomes of the WeFold project, which brings together the world's top experts in the field, indicate that satisfactory solutions are yet to emerge [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cursory analysis of to-date results suggests that progress has so far been fairly limited [3]. Similarly, the recently published outcomes of the WeFold project, which brings together the world's top experts in the field, indicate that satisfactory solutions are yet to emerge [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our physicsbased approach to protein-structure prediction, that uses the UNRES force field, performed reasonably well in biannual CASP Community Wide Experiment on the Critical Assessment of Techniques for Protein Structure Prediction, exercises to obtain fold topology, e.g. for targets T0061, T0063 and T0079 in CASP3 (Lee et al, 1999(Lee et al, , 2000, T0102 in CASP4 (Liwo et al, 2011), T0129 andT0149 in CASP5, T0215, T0223, T0230 andT0281 in CASP6 (Ołdziej et al, 2005), T0534, T0537 and T0578 in CASP9 (Liwo et al, 2011) and T0644, T0663, T0668 and T0740 in CASP10 (He et al, 2013;Khoury et al, 2014). However, because the UNRES predictions are generally of medium-resolution quality, which is remarkably lower than those for TBM targets, UNRES was featured only for new-fold targets (proteins with unique orientation of the local structure) and for targets with new types of domain packing.…”
Section: Introductionmentioning
confidence: 99%
“…The first one was a two-domain target T0663 (treated by the Cornell-Gdansk group) (He et al, 2013), and the second one was T0740 (treated by the wfCPUNK group within the WeFold initiative) (Khoury et al, 2014); in the second prediction exercise, UNRES was supplemented with contact-prediction restraints. In the CASP10 experiment, we proved that the UNRES force field is a very good tool to predict the orientation of the domains for the 2-fold symmetry target T0663 (He et al, 2013) that was further confirmed by post-CASP tests with use of restraints within the domains, but not between them (Krupa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, o projeto WeFold aplica a metodologia denominada "coopetition": a cooperação de vários grupos, cada com os seus métodos aplicados ao PSP (KHOURY et al, 2014). Os participantes do WeFold competem e cooperam entre si, combinando os diferentes componentes e abordagens dos programas utilizados por cada um, para a geração de um novo sistema, integrando diversos programas para a geração de um sistema mais completo.…”
Section: Motivação E Relevância Do Trabalhounclassified
“…Os participantes do WeFold competem e cooperam entre si, combinando os diferentes componentes e abordagens dos programas utilizados por cada um, para a geração de um novo sistema, integrando diversos programas para a geração de um sistema mais completo. O resultado dessa "coopetition" foi testado no CASP10 (2012) conseguindo bons resultados (KHOURY et al, 2014).…”
Section: Motivação E Relevância Do Trabalhounclassified